Correlation between bacterial vaginosis and adverse obstetric outcomes in Brazilian women - Monteiro, Michelly Nóbrega; Cobucci, Ricardo Ney Oliveira; Queiroz, Janice; Lucena, Eudes Euler de Souza; Vital, Ana Luísa Fernandes; Gonçalves, Ana Katherine; Palitot, Tatyane Ribeiro de Castro; Eleutério Junior, José; Giraldo, Paulo César (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: Vaginal infections and modifications in the vaginal flora are very prevalent during pregnancy and have been associated with adverse obstetric outcomes, such as preterm labor, preterm premature rupture of membranes and low birth weight. Objective: To evaluate the prevalence and associations of bacterial vaginosis (BV) and pregnancy outcomes among Brazilian pregnant women in the third trimester. Methods: A prospective observational study was conducted assessing vaginal microbiota on bacterioscopy (wet mount and Gram stain), using vaginal swabs obtained from pregnant women between 26 and 32 weeks’ gestation. The women were monitored until delivery, and their pregnancy outcome and demographic data were collected using an interviewer-administered questionnaire. Results: BV was assessed using both Amsel’s criteria and Nugent’s score in 77 of 190 women, resulting in the prevalence of 42.5%. BV was significantly associated with preterm labor (risk ratio [RR], 2.89; 95% confidence interval [CI], 2.35–3.56) and low birth weight (RR, 2.17; 95%CI, 1.61–2.92). Premature rupture of membranes was not associated with BV. Conclusion: BV was found to be very frequent among Brazilian pregnant women in the third trimester and correlated to unfortunate pregnancy outcomes. Regular screening of pregnant women may allow for early treatment and prevention of some obstetric complications